2000
DOI: 10.1038/35023233
|View full text |Cite
|
Sign up to set email alerts
|

Pushing the limits of lithography

Abstract: The phenomenal rate of increase in the integration density of silicon chips has been sustained in large part by advances in optical lithography--the process that patterns and guides the fabrication of the component semiconductor devices and circuitry. Although the introduction of shorter-wavelength light sources and resolution-enhancement techniques should help maintain the current rate of device miniaturization for several more years, a point will be reached where optical lithography can no longer attain the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
551
0
6

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 779 publications
(557 citation statements)
references
References 15 publications
0
551
0
6
Order By: Relevance
“…86 Electron-and ion-beam lithography offer high resolution control of features, but these methods are also low-throughput and expensive. [86][87][88] Photolithography is a highthroughput and relatively inexpensive method that allows the controlled fabrication of patterned structures, but objects that are created by photolithography can be no smaller than the diffraction limit of the optical device used during the exposure step. 89 Efforts to overcome this restraint include reaching further into the ultraviolet light range or using X-ray lithography.…”
Section: Controlled Silver Nanoparticle Dissolution Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…86 Electron-and ion-beam lithography offer high resolution control of features, but these methods are also low-throughput and expensive. [86][87][88] Photolithography is a highthroughput and relatively inexpensive method that allows the controlled fabrication of patterned structures, but objects that are created by photolithography can be no smaller than the diffraction limit of the optical device used during the exposure step. 89 Efforts to overcome this restraint include reaching further into the ultraviolet light range or using X-ray lithography.…”
Section: Controlled Silver Nanoparticle Dissolution Experimentsmentioning
confidence: 99%
“…89 Efforts to overcome this restraint include reaching further into the ultraviolet light range or using X-ray lithography. 87,89 For the purposes of this study, nanosphere lithography (NSL) has been chosen since it is a versatile, inexpensive, and high-throughput lithographic technique. 86…”
Section: Controlled Silver Nanoparticle Dissolution Experimentsmentioning
confidence: 99%
“…The directed-or selfassembly of particles, also known as the ''bottom-up'' strategy, has great potential to overcome size limitations and processing restrictions of current ''top-down'' manufacturing processes, such as photolithography. [32][33][34][35] The anisotropic nature of the patchy particle surface enables a certain degree of control over the assembly process, since the specific interactions with and between patches can provide a driving force for assembly of a targeted structure. Several computational studies on the self-assembly of patchy particles have been reported and these have pushed the imagination of the patchy particle community to new heights.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in semiconductor architectures, nanorod ensembles allow for potential miniaturization significantly beyond the lithographic limit. 8 Spherical, columnar and branched nanocrystals have been shown to exhibit single electron transistor behaviour. [9][10][11] Vertical alignment of semiconductor nanorods in an organised assembly would potentially allow each rod (single electron transitor) in a 2D array to be contacted individually at the end facet for macroscopic integration at < 5 nm separation.…”
mentioning
confidence: 99%